The impact of social networks on rural residents’ engagement in living environment upgrade: An integrated analysis drawing on social network theory and the theory of planned behavior - Gulsanam Amat; Jing Wang (PLoS ONE, 2025)
The issue of rural living environment is a critical concern for China and the global community, intricately intertwined with regional economic development. The proactive involvement of rural residents, who are both beneficiaries and influencers of the environment, constitutes a cornerstone in improving environmental standards. Therefore, the factors that shape rural residents’ participation in living environment upgrade must be explored. Drawing upon the theory of planned behavior and social capital theory, this study employs a structural equation model (SEM) to comprehensively examine the determinants of rural residents’ engagement in living environment upgrade, utilizing data from 334 households in Hebei Province, China. The findings can be summarized as follows: (1) Social networks, subjective norms, perceived behavioral control, and attitudes towards behavior significantly and positively impact rural residents’ engagement in upgrading the living environment, (2) Attitudes towards behavior act as mediators between perceived behavioral control and rural residents’ engagement in living environment upgrade, as well as between subjective norms and rural residents’ engagement in living environmental upgrade. (3) Social networks could indirectly influence rural residents’ engagement in living environment upgrade through the independent mediating effect of subjective norms and attitudes towards behavior, as well as through the chain mediating effect of the two. In conclusion, several managerial recommendations are proposed to stimulate rural residents’ active participation in living environment upgrade.